Methicillin-Resistant Staphylococcus aureus pada Penderita Dermatitis Atopik dan Sensitivitasnya terhadap Mupirosin Dibandingkan dengan Gentamisin - Keni Istasaputri M.; Endang Sutedja; Oki Suwarsa; Sunarjati Sudigdoadi (Majalah Kedokteran Bandung, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) is found in moderate to severe atopic dermatitis (AD) and is multiresistant against topical antibiotic. Gentamycin is widely used while mupirocin is the first line therapy to eliminate MRSA. This research is intended to observe the colonization of MSRA case in AD patients and its sensitivity to mupirocin compared to gentamycin in Dermato-venereology Clinic Dr. Hasan Sadikin General Hospital Bandung. An analytical cross sectional survey was intended from 19th September–31st October 2011 in 22 moderate to severe AD patients based on objective Scoring Atopic Dermatitis and 22 healthy persons. All subjects went through skin-scraping, MSRA was detected and sensitivity test was done for mupirocin and gentamycin. The subjects consisted of 10 boys and 12 girls in both group. Based on severity, 10/22 of AD subjects were in moderate AD and 12/22 were severe AD, 14/22 of AD subjects presented with acute lesions and 8/22 subjects had chronic lesions. In the group of AD patients, 17/22 growth of S. aureus were found with sensitivity against mupirocin 14/17 and gentamycin 11/17. In healthy individual group, no S. aureus growth was found. Methicillin-resistant Staphylococcus aureus strain in AD patients was observed on 3/17 patients, and this was declared significantly different compared to healthy individuals (p <0.01). The isolates in 2/3 patients were sensitive to mupirocin and all patients were resistant to gentamycin. In conclusion, the patients of moderate to severe AD are prone to MRSA colonization and therefore requires mupirocin topical antibiotic treatment.